Graphitisation of waste carbon powder with femtosecond laser annealing - Lum, Lucas (2022)
Graphitisation of structural characteristics and improvement in electrical conductivity was reported onto waste carbon powder through femtosecond laser annealing. Raman spectroscopy on the carbon powder pre- and post-annealing showed a shift from amorphous-like carbon to graphitic-like carbon, which can be explained by the three-stage model. Electrical I-V probing of the samples revealed an increase in conductivity by up to 90%. An increase in incident laser power was found to be correlated to an increase in conductivity. An average incident laser power of 0.104 W or less showed little to no change in electrical characteristics, while an average incident laser power of greater than 1.626 W had a destructive effect on the carbon powder, shown through the reduction in powder. The most significant improvement in electrical conductivity has been observed at laser powers ranging from 0.526 to 1.286 W. To conclude, the graphitisation of waste carbon powder is possible using post-process femtosecond laser annealing to alter its electrical conductivity for future applications.